The Perceptions and Attitudes of Dentists Towards Cone-Beam Computed Tomography Reports - Melih Özdede; İlkay Peker; Özlem Üçok; Bülent Altunkaynak (Cumhuriyet University, 2018)
Objectives: Radiology reports are the most important method of communication between the clinician and the radiologist. In dentomaxillofacial radiology, cone-beam computed tomography (CBCT) reporting is a new subject. The purpose of this study was to evaluate the satisfaction and expectations of dentists from CBCT reporting as well as contributing to standardization and improvement in the quality of CBCT reports. Materials and Methods: Dentists were invited to participate in the survey by e-mail. The participants filled out a survey with their demographic data and responded to 14 questions regarding CBCT reports. The responses regarding gender, age, title, institution, and department were analysed and compared with chi-square tests. Results: In total, 185 dentists (97 females and 88 males) participated in the study. Participants reported that the adequacy level of the reports were mostly moderate (47%) and that the source of adequate reports was university hospitals (49.2%). Most dentists (57%) reported that they needed a consultant radiologist in clinical practice on a part time basis. There was a statistically significant difference (p<0.05) between participants' genders, age groups, titles, and departments regarding the source of the adequate reports. Conclusions: The results of this study showed that most of the dentists were not satisfied about the proficiency of CBCT reports. More than half of those surveyed thought that "not reading" the radiology reports might give them a legal liability. Most dentists wanted to consult with the radiologist before and after patient examinations.